The 33 M[symbol sun] black hole Gaia BH3 is part of the disrupted ED-2 star cluster - Balbinot, Eduardo; Dodd, E.; Matsuno, Tadafumi; Lardo, C.; Helmi, A.; Panuzzo, P.; Mazeh, T.; Holl, B.; Caffau, E.; Jorissen, A.; Babusiaux, C.; Gavras, P.; et al. (Astronomy and astrophysics, 2024)
Context. The Gaia Collaboration has recently reported the detection of a 33 M⊙ black hole in a wide binary system located in the solar neighbourhood. Aims. Here we explore the relationship between this black hole, known as Gaia BH3, and the nearby ED-2 halo stellar stream. Methods. We studied the orbital characteristics of the Gaia BH3 binary and present measurements of the chemical abundances of ED-2 member stars derived from high-resolution spectra obtained with the VLT. Results. We find that the Galactic orbit of the Gaia BH3 system and its metallicity are entirely consistent with being part of the ED-2 stream. The characteristics of the stream, particularly its negligible spread in metallicity and in other chemical elements, as well as its single stellar population, suggest that it originated from a disrupted star cluster of low mass. Its age is comparable to that of the globular cluster M92 that has been estimated to be as old as the Universe. Conclusions. This is the first black hole unambiguously associated with a disrupted star cluster. We infer the plausible mass range for the cluster to be relatively narrow, between 2 × 10 3 M⊙ and 5.2 × 10 4 M⊙. This implies that the black hole could have formed directly from the collapse of a massive very metal-poor star, but that the alternative scenario of binary interactions inside the cluster environment also deserves to be explored.